Analysis of Social Media Innovation Tiktok as a Promotional Media in Creating Competitiveness (Competitive Adventage) in the Sustainability of UMKM BerkahFD Gorden Kediri - Mauludin, Mohamad Mauludin (Universitas Nusantara PGRI Kediri, 2025)
Research aim :This study aims to analyze the innovation of using TikTok social media as a promotional media in creating competitiveness and business sustainability at UMKM BerkahFD Gorden Kediri. Design/Method/Approach :The study used a qualitative method with indepth interviews with MSME owners and consumers, supported by thematic analysis based on the 4P's of Innovation (Product, Process, Position, Paradigm) as follows: Research Preparation Determine the research objectives and formulate research questions. Participant Selection Determine the selection criteria and recruit relevant MSME owners and consumers. Data Collection Conduct in-depth interviews with participants to collect information related to innovation in the aspects of Product, Process, Position, and Paradigm. Thematic Analysis Identify themes that emerge from interview data, group information based on the 4P's of Innovation. Reporting Results Compile a research report that includes methodology, findings, and conclusions. Research Findings :The results show that TikTok contributes significantly to increasing product visibility and business competitiveness through creative, interactive content and relevant digital trends. TikTok-based strategies allow for cost-efficient promotion while reaching a wider audience. Theoretical contribution/Originality :This study enriches the literature on the implementation of 4P's of Innovation in digital marketing, especially through TikTok social media for MSMEs in Indonesia. Practitionel/Policy implications:These findings provide practical guidance for MSMEs in utilizing TikTok to improve business sustainability, while also providing recommendations for policy makers to support MSME digital transformation. Research limitations:This research is limited to one MSME in Kediri, so the results may not fully represent other MSMEs with different contexts. Keywords :MSME, TikTok, digital marketing, innovation, competitiveness, promotion.